Influence of Depressive Symptoms on the Outcome of Lumbar Spine Fusion—A 5-year Follow-up Study. Issue 6 (15th March 2021) - Toivonen, Leevi; Häkkinen, Arja; Pekkanen, Liisa; Salonen, Anne; Kautiainen, Hannu; Neva, Marko H.
Abstract : The influence of depressive symptoms on the outcome of lumbar spine fusion surgery was analyzed in a 5-year follow-up study. Depressive symptoms diminished to one-third shortly after surgery, and partially re-appeared in 5 years. Patients with depressive symptoms and those without seemed to benefit equally from LSF. Abstract : Study Design: Prospective follow-up study. Objective: The aim of this study was to assess whether depressive symptoms change the outcome of lumbar spine fusion (LSF) surgery at a 5-year follow-up. Summary of Background Data: Previous reports of the influence of depressive symptoms on the results of spine surgery are controversial, but the patient characteristics and indications for surgery varied widely between the studies. The influence of depressive symptoms on the 5-year outcome of LSF has not been studied. Methods: The study was based on data from a local LSF database from two hospitals comprising 392 consecutive patients (mean age 61 years, 277 women) who underwent an instrumented LSF and fulfilled the 5-year follow-up. At the 5-year follow-up, the patients were compared with a control group from the general population (n = 477, age-, sex-, and residential area-matched) extracted from Official Statistics of Finland. The prevalence of depressive symptoms was evaluated using the Depression Scale (DEPS; 0–30) and disability was evaluated by the Oswestry Disability Index (ODI; 0–100%). A DEPS score ≥12 was considered to indicate depressive symptoms. Results: Before surgery, 35% of the patients had depressive symptoms. The proportion diminished to 13% at 3 months postoperatively and increased to 24% at 5 years. In the population, the prevalence was 11% at baseline and 10% at the 5-year follow-up. The preoperative ODI was 54 in the patients with depressive symptoms, and it was 41 in the patients with no depressive symptoms. The changes at 5-year follow-up were −20 and −18, correspondingly. The same congruence was preserved when analyzing short and long fusions separately. These changes were statistically and clinically significant. In the control population, the ODI remained around 24 in depressive people and 10 in nondepressive people. Conclusion: Our data suggest that patients with and without depressive symptoms may benefit equally well from LSF. Level of Evidence: 3